Condições de saúde bucal em um município brasileiro - Martins, Heron Ataide (2019)
Epidemiological surveys are important for obtaining information on the prevalence and etiology of oral diseases. From the collected data, it is possible to plan, execute and evaluate oral health actions and interventions in the municipality. Thus, the objective of this work was to evaluate the main oral health conditions in 5 and 12 years old students from a Brazilian city. A cross-sectional observational study in which 453 children from public schools in the urban area of Alfenas/MG. The research variables were: at 5 years the prevalence and severity of crown dental caries and the prevalence of occlusions; and at age 12 the periodontal condition, the prevalence and severity of dental fluorosis, and the prevalence of dental trauma. Research data collection occurred in school units, following all ethical recommendations for this type of study. A calibration training for each oral condition was performed with public dentists and assistants, and the result was an overall inter-examiner agreement of 93,8% and a kappa coefficient of 0,86. For the epidemiological exams, natural lighting was used and according to the criteria recommended by SB Brasil 2010 - Oral Health Conditions of the Brazilian Population. A retrospective descriptive study of the municipality (2008 - 2018), based on oral health information available in public information systems complemented the data analysis. The prevalence of crown dental caries at 5 years (N = 215) was 49,77%, and at 12 years (N = 238), it was 69,33%. The DMFT index at 5 and 12 years of age were 1,93 (1,59-2,32) and 2,13 (2,01-2,64), respectively, with a predominance of the component dental caries for both ages. The most frequent treatment needed for dental caries was 12-year single-surface restorations and 5-year two or more surface restorations. In the results of the occlusal condition, 68,84% of 5-year-old children present at least one change that required assistance, with overjet (28,16%) and overbite (53,81%) being more prevalent; and at 12 years the prevalence of defined, severe and very severe occlusion was 22,69%, 12,18% and 9,66%, respectively. In the other oral health conditions surveyed at 12 years old 69,33% presented all healthy sextants, and the presence of dental calculus was the worst periodontal condition observed (24,37%), with the central lower sextant most affected (21,85%). At the age of 12, only 2.15% with dental traumatic injuries and 10.92% children with very mild fluorosis were identified. Finally, the indicators of utilization of dental services demonstrated a reduction in collective preventive procedures and, in contrast, an increase in individual emergency dental dressings, even with a high coverage of oral health in primary health care. The present study pointed to a growing tendency of the prevalence and severity of dental caries with advancing age, as well as a high prevalence of occlusions at both ages. Also, found a reduction in the indicators of dental services, especially collective preventive and maintenance of the curative-mutilator model. Given these results, preventive and care measures for dental caries and occlusal conditions should be implemented, as well as a change in the model of oral health care.